The social world of the sages : an introduction to Israelite and Jewish wisdom literature - Sneed, Mark R. (Minneapolis, Fortress Press, 2015)
Is there evidence for a distinct "wisdom tradition" in ancient Israel? Mark R. Sneed redefines the wisdom literature as a loosely cohering collection of books that educated scribal apprentices in moral instruction. Sneed discusses the data for scribal culture and pedagogy in the ancient Near East, suggesting that wisdom literature was meant to complement, not to compete with, other modes of literature in the Hebrew Bible. The result is a surprising new picture of the authors and tradents of the wisdom literature. From back cover
The nature of wisdom and its practitioners -- The world and worldview of the wise: an anthropological approach -- Scribalism in Egypt and Mesopotamia -- Western periphery scribalism -- Israelite scribalism and the place of wisdom literature within it -- The wisdom corpus as a mode of literature -- The poetics, axiology, and rhetoric of wisdom literature -- Social world of the sages -- The book of Proverbs -- The book of Job -- Ecclesiastes -- Sirach and Sapientia -- Wisdom Psalms and the Dead Sea Scroll wisdom literature.
Includes bibliographical reference (pages 397-421) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Dead Sea scrolls; Wisdom literature -- Criticism, interpretation, etc; Criticism, interpretation, etc